2020
DOI: 10.26599/jnr.2020.9040017
|View full text |Cite
|
Sign up to set email alerts
|

Vagal nerve stimulation is effective in pre-school children with intractable epilepsy: A report of two cases

Abstract: There is lack of prospective evidence regarding vagal nerve stimulator (VNS) in younger children with intractable epilepsy. Here, we report the outcomes of using VNS in two pre-school patients for pediatric intractable epilepsy (VNS-PIE) study. Medical treatment was ineffective in both the patients, and they underwent VNS implantation. Seizure frequency, score on the Gesell scale, and heart rate variability (HRV) were assessed following VNS therapy. After 6 months VNS treatment, the seizure frequency in the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It is generally acknowledged that epilepsy surgery and neuromodulation surgery are effective therapies to treat refractory epilepsy [3,4]. Recent studies have shown that neurostimulation has also become one of the effective therapies for refractory epilepsy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally acknowledged that epilepsy surgery and neuromodulation surgery are effective therapies to treat refractory epilepsy [3,4]. Recent studies have shown that neurostimulation has also become one of the effective therapies for refractory epilepsy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Focal cortical dysplasia (FCD) is a specific cortical malformation occurred during the development and represents the most prevalent etiology of medically intractable epilepsy in children, leading to surgical resection of the lesions or neurostimulation treatment ultimately [1,2]. FCD is classified into type I and type II according to the current international consensus classification by ILAE [3].…”
Section: Introductionmentioning
confidence: 99%